Neurophysiology of spontaneous facial expressions: I. Motor control of the upper and lower face is behaviorally independent in adults. (March 2016) - Ross, Elliott D.; Gupta, Smita S.; Adnan, Asif M.; Holden, Thomas L.; Havlicek, Joseph; Radhakrishnan, Sridhar
Abstract: Facial expressions are described traditionally as monolithic entities. However, humans have the capacity to produce facial blends, in which the upper and lower face simultaneously display different emotional expressions. This, in turn, has led to the Component Theory of facial expressions. Recent neuroanatomical studies in monkeys have demonstrated that there are separate cortical motor areas for controlling the upper and lower face that, presumably, also occur in humans. The lower face is represented on the posterior ventrolateral surface of the frontal lobes in the primary motor and premotor cortices and the upper face is represented on the medial surface of the posterior frontal lobes in the supplementary motor and anterior cingulate cortices. Our laboratory has been engaged in a series of studies exploring the perception and production of facial blends. Using high-speed videography, we began measuring the temporal aspects of facial expressions to develop a more complete understanding of the neurophysiology underlying facial expressions and facial blends. The goal of the research presented here was to determine if spontaneous facial expressions in adults are predominantly monolithic or exhibit independent motor control of the upper and lower face. We found that spontaneous facial expressions are very complex and that the motor control of the upper and lower face is overwhelmingly independent, thus robustly supporting the Component Theory of facial expressions. Seemingly monolithic expressions, be they full facial or facial blends, are most likely the result of a timing coincident rather than a synchronous coordination between the ventrolateral and medial cortical motor areas responsible for controlling the lower and upper face, respectively. In addition, we found evidence that the right and left face may also exhibit independent motor control, thus supporting the concept that spontaneous facial expressions are organized predominantly across the horizontal facial axis and secondarily across the vertical axis.